The real value of China's stock market - Jennifer N. Carpenter; Fangzhou Lu; Robert F. Whitelaw (Bank of Finland, Institute for Economies in Transition (BOFIT), 2018)
This paper shows that, counter to common perception, stock prices in China are strongly linked to firm fundamentals. Since the reforms of the early 2000s, stock prices are as informative about future profits as they are in the US. Although the market is segmented from international equity markets, Chinese investors price individual stock characteristics like other global investors: they pay up for size, growth, liquidity, and long shots, while they discount for systematic risk. Price informativeness is significantly correlated with corporate investment e ciency. For international investors, China's stock market offers high average returns and low correlation with other equity markets.
URN:NBN:fi:bof-201801221106
Keywords: E44; F30; G12; G14; G15; O16; O53; P21; P34; 330